Implementasi Nilai Pancasila Dalam Membangun Kesatuan Bangsa Ditengah Polemik Covid-19 di Yayasan Darul Furqon Ramadhan Bogor - Mohamad Anwar; Pendi Ahmad; Turkamun Turkamun; Sylvia Hasanah Thorik; Nani Widya Sari (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
By carrying out Community Service (PKM) with the theme Implementation of Pancasila Values in Building Nation Unity in the Midst of Polemic Covide-19 at the Darul Furqon Ramadhan Foundation in Bogor, in addition to fulfilling the duties of the Tri Dharma of Higher Education, the service team also had the opportunity to provide material presentation on the implementation of the Darul Furqon Ramadhan Foundation in Bogor. Pancasil values to the management of foundations and students in the midst of the co-19 polemic while still obeying the rules set by the government. The importance of understanding and implementing Pancasila values for the foundation's management and students is needed to ensure that reducing physical contact and going out of the house is one of the things included in applying the value of the Pancasila of the Indonesian Unity. Pancasila as the basis of the state and also as a characteristic of the Indonesian nation cannot be separated from community activities in carrying out daily activities as well as in handling a problem. Therefore, a deeper understanding of the values of Pancasila is the most important thing in the pre-emptive effort so that the board administrators and students at the Darul Furqon Ramadhan Foundation. does not violate government regulations related to the settlement and handling of Covid-19 in Indonesia. At the end of the Community Service activity, it was closed with a photo with the head of the foundation, students, local residents and D3 lecturer at the University of Pamulang Secretariat. Hopefully what has been done together can bring blessings to all of us, it is never too late to fulfill our duties and responsibilities to move forward together to maintain a sense of unity and mutual ownership.Keywords: Pancasila Values, National Unity, and Covid-19 Polemic